Transition into daylight saving time influences the fragmentation of the rest-activity cycle - Tuulio-Henriksson Annamari (Journal of Circadian Rhythms, 2006)
Abstract Background Daylight saving time is widely adopted. Little is known about its influence on the daily rest-activity cycles. We decided to explore the effects of transition into daylight saving time on the circadian rhythm of activity. Methods We monitored the rest-activity cycles with the use of wrist-worn accelerometer on a sample of ten healthy adults for ten days around the transition into summer time. Identical protocols were carried out on the same individuals in two consecutive years, yielding data on 200 person-days for analysis in this study. Results There was no significant effect on the rest-activity cycle in the sample as a whole. Fragmentation of the rest-activity cycle was enhanced in a subgroup of persons having sleep for eight hours or less (P = 0.04) but reduced in those who preferred to sleep for more than eight hours per night (P = 0.05). The average level of motor activity was increased in persons having the morning preference for daily activity patterns (P = 0.01). Conclusion Transition into daylight saving time may have a disruptive effect on the rest-activity cycle in those healthy adults who are short-sleepers or more of the evening type.